1999
DOI: 10.1016/s0014-5793(99)00204-5
|View full text |Cite
|
Sign up to set email alerts
|

Cell membrane dynamics and the induction of apoptosis by lipid compounds

Abstract: To investigate the induction of apoptosis by some lipid compounds which are a potent inducer of apoptosis, the plasma membrane fluidity of U937 cells was measured using the fluorescent probe, pyrene. The increase of the membrane fluidity was observed immediately after the treatment of cells with lipid inducers. We also found that the trigger of apoptosis was pulled within 30 min after treatment. Data from the dynamic light scattering experiment indicated that lipid inducers were dissolved to form the emulsion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 25 publications
(25 reference statements)
2
30
0
1
Order By: Relevance
“…The increase of hepatocytes membrane fluidity under the influence of some xenobiotics (such as tacrine, ximelagatran or ethanol) is related to drug-induced liver injury and is leading to substantial disturbances of cell function (Sergent et al 2005(Sergent et al , 2009). Fujimoto et al (1999) proved that cells exposed to apoptotic stimuli exhibit alterations of membrane fluidity. The viral infection of N2a mouse neuroblastoma cells leads to a significant increase in membrane fluidity (Mishra et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The increase of hepatocytes membrane fluidity under the influence of some xenobiotics (such as tacrine, ximelagatran or ethanol) is related to drug-induced liver injury and is leading to substantial disturbances of cell function (Sergent et al 2005(Sergent et al , 2009). Fujimoto et al (1999) proved that cells exposed to apoptotic stimuli exhibit alterations of membrane fluidity. The viral infection of N2a mouse neuroblastoma cells leads to a significant increase in membrane fluidity (Mishra et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Increased membrane fluidity of A549 cells treated with DMTreC14 was obtained on the basis of the fluorescence polarization (P) analysis. Enhanced fluidity of cell membrane in the apoptosis for tumor cells has been reported [18,19]. These results suggest that DMTreC14 fused into A549 cells and then increased fluidity of the cell membrane.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, the anti-invasive effects of DMTreC14 were observed at low concentrations (40 μM) without affecting growthinhibition. Actin cytoskeleton dynamics, such as lamellipodia and filopodia formation on the surface of tumor cells plays an important role in the invasion and migration into the surrounding tissue [18][19][20][21][22]. The treatment with DMTreC14 drastically inhibited the filopodia formation in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that this compound induces apoptosis in rat glioma C6 cells and human monoblastic leukemia U937 cells (Yasugi et al ., 1995;Dohi et al ., 1996;Fujimoto et al ., 2000). In Dol-P treated U937 cells, increase of plasma membrane fluidity (5-20 min) (Fujimoto et al ., 1999), reduction in ∆ψ m (1 hr) and translocation of apoptosis-inducing factor (3 hr) , increase of caspase-3-like protease activity (2-4 hr) (Yokoyama et al ., 1997;Yasugi et al ., 1998), chromatin condensation and DNA ladder formation (3-4 hr) were observed successively (Yasugi et al ., 1995). From the effects of specific inhibitors of caspases, we speculate at least two redundant parallel pathways may lead to chromatin processing during Dol-Pinduced apoptosis.…”
Section: Introductionmentioning
confidence: 98%